Alumni Future Business IMR652 E-Magazine: 30 March 2023 - Bunsu, Arith Syakir; Daniel, Nur Zafika; Ramsa, Rizwanshah; -, Siti Nur Syazwanie; Empang Wan, Veronica (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
First and foremost, I believe it is never too late for me to wish everyone a happy and promising new year 2023. Since we are still threatened by the viruses of post Covid-19 pandemic, we must continue to observe our SOPs and never take this virus for granted. This e-magazine is mainly focusing on Management of Business Records and how it is related to the Alumni as its core business. The Alumni can help with global admissions and recruitment efforts, career and professional development, local and state advocacy or lobbying and through their generous philanthropic support. All articles and write-ups included in this e-publication are based on research or non academic research of the university. The purpose of publishing this e-magazine is to strenghten the engagement of the alumni in university and how to strengthen this relationship so that we can create meaningful values in return to our graduates. One of the best parts of being part of an alumni association is the network that comes with it. An alumni network connects you, as a graduate, with a number of professional contacts and other graduates from your university. "Being willing to share the lessons learned on your journey, strategies for meeting challenges, and find opportunities for growth and connection are a few good moves. It all starts with a question, ‘Hello, how can I help you?’” Last but not least, strike for the best and strive for excellence throughout our most productive year in UiTM.